On the role of allergen-specific IgG subclasses for blocking human basophil activation - Zinkhan, Simon; Thoms, Franziska; Augusto, Gilles; Vogel, Monique; Bachmann, Martin F. (Frontiers in Immunology, 2022)
Successful treatment of IgE mediated allergies by allergen-specific immunotherapy (AIT) usually correlates with the induction of allergen-specific IgG4. However, it is not clear whether IgG4 prevents the allergic reaction more efficiently than other IgG subclasses. Here we aimed to compare allergen-specific monoclonal IgG1 and IgG4 antibodies in their capacity to inhibit type I allergic reactions by engaging FcRIIb. We found that IgG1, which is the dominant subclass induced by viruses, binds with a similar affinity to the FcRIIb as IgG4 and is comparable at blocking human basophil activation from allergic patients; both by neutralizing the allergen as well as engaging the inhibitory receptor FcRIIb. Hence, the IgG subclass plays a limited role for the protective efficacy of AIT even if IgG4 is considered the best correlate of protection, most likely simply because it is the dominant subclass induced by classical AITs.